Adaptive Sensing Relevance Exploiting Social Media Mining in Smart Cities - Andrade, Daniel C.; Costa, Daniel G.; Rocha-Junior, João B. Rocha (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
Wireless sensor networks are an important part of smart cities, but there are still many challenging issues, demanding optimizations in those networks for higher efficiency. Events of interest may be identified analyzing data posted in social media, and such events may be used to assign priority levels to sensor nodes. This paper proposes an automatic mechanism to update sensors’ priorities based on events mined and identified in social medias, which may be then optimized for higher monitoring efficiency.